Accounting for personhood in palliative sedation: the Ring Theory of Personhood. Issue 1 (26th September 2013) - Radha Krishna, Lalit Kumar
Abstract : Application of sedation at the end of life has been fraught with ethical and clinical concerns, primarily focused on its potential to hasten death. However, in the face of clinical data that assuage most of these concerns, a new threat to this treatment of last resort has arisen. Concern now pivots on its effects on the personhood of the patient, underpinned by the manner in which personhood has been conceptualised. For many authors, it is consciousness that is seen to be the seat of personhood, thus its loss is seen to rob a patient of their moral and ethical worth, leaving them in a state that cannot ethically be differentiated from death. Here I proffer a clinically based alternative to this view, the Ring Theory of Personhood, which dispels these concerns about sedation at the end of life. The Ring Theory envisages personhood as a coadunation of three domains of concern: the innate, the individual and the relational elements of personhood. The innate element of personhood is held to be present among all humans by virtue of their links with the Divine and or their human characteristics. The individual elements of personhood pivot on the presence of consciousness-dependent features such as self-awareness, self-determination and personality traits. The relational component of personhood envisages an individual as being 'socially embedded' replete with social and familial ties. It is these three equally important inter-related domains that define personhood.